Risk-related disclosure practices in the annual reports of Portuguese credit institutions: an exploratory study - Oliveira, Jonas (2011)
This study assesses the risk-related reporting practices of 190 Portuguese credit institutions based on a content analysis of their individual annual reports for 2006. Risk-related disclosures are found to lack comparability because of different maturity time bands that report exposures to credit, market and liquidity risks; different VaR and sensitivity analysis assumptions; and different practices for reporting capital structure and adequacy. The mis-alignment of quantitatively-based disclosures and related narratives led to problems of relevance, reliability and understandability. We assess the extent to which reforms of risk-related reporting practices in 2007 in International Financial Reporting Standards and the BASEL II Accord address each of the deficiencies identified. We highlight areas needing further reform and recommend that Portuguese supervisory authorities adopt more effective enforcement mechanisms to broker compliance with minimum mandatory risk disclosure requirements.